Análisis de los dominios ético; legal y económico de la responsabilidad social empresarial: un caso empresarial. (2013)
The tendency of organizations is to achieve positioning and legitimacy through strategies of corporate social responsibility (CSR). This article focuses on the analysis of CSR practices and it seeks; through a business case; to define a method to examine the benefits of its application in society and in organizations. From the proposal of Schwartz (2011) on the domains of corporate social responsibility; where the ethical; economic; and legal dimensions of philanthropic organizations converge; financial reports and social balances of a company; were studied; where we identified; financial; ethical; and tax variables which allowed us to establish the orientation and balance between social responsibility practices and corporate image.